Xanthan Gum as a Carrier of Preservative Agents and Calcium Chloride Applied on Fresh‐Cut Apple. Issue 3 (10th June 2013) - Freitas, Irene Rodrigues; Cortez‐Vega, William Renzo; Pizato, Sandriane; Prentice‐Hernández, Carlos; Borges, Caroline Dellinghausen
Abstract This study aimed to evaluate xanthan gum as a carrier of preservative solution and calcium chloride in edible coating applied to fresh‐cut apple. The utilized coatings, prepared in aqueous solution, were: (T1) control, (T2) 1% glycerol, (T3) 1% glycerol and 0.5% xanthan gum, (T4) 1% glycerol, 0.5% xanthan gum and 1% CaCl2 (T5) 1% CaCl2 (T6) 1% ascorbic acid and 0.25% citric acid, (T7) 1% glycerol, 0.5% xanthan gum, 1% ascorbic acid and 0.25% citric acid (T8) 1% glycerol, 0.5% xanthan gum, 1% CaCl2, 1% ascorbic acid and 0.25% citric acid. The T8 treatment presented the best combination of results, with reduction of mass loss and oxidative browning, increase of firmness, lower growth of psychrotrophic microorganisms, molds and yeasts, and absence of total and thermotolerant coliforms, Escherichia coli and Salmonella sp. Practical Applications Fresh‐cut apples are appreciated worldwide for their flavor and nutritional composition. However, their shelf life is limited by changes in color, texture, appearance and microbial growth. An alternative to try to minimize the losses and increase the shelf life of this product is the use of edible coatings, maintaining the quality parameters of fresh fruit. Xanthan gum, a thickening agent, can be used as a carrier of preservative solution (citric and ascorbic acid) and calcium chloride to be used in edible coating in fresh‐cut apples. It can be considered useful to the minimal processing industry and used as an alternative to fast food and other ready‐to‐eat products, attending the demand for healthy and convenient foodstuffs.